Effect of Solvents and Stabilizer Molar Ratio on the Growth Orientation of Sol-Gel-Derived ZnO Thin Films. (21st February 2019) - Bekkari, R.; Jaber, B.; Labrim, H.; Ouafi, M.; Zayyoun, N.; Laânab, L.
Abstract : This work targets to control the growth orientation of sol-gel-derived ZnO thin films in order to allow different modes of excitation (longitudinal and transverse) when targeted to be used in piezoelectric applications. For that, the effect of solvents and stabilizer molar ratio on the structural and optical characteristics of the obtained films is investigated by means of X-ray diffraction (XRD), scanning electron microscopy (SEM), and UV-Vis spectrophotometry. The XRD results show clearly that the synthesized films exhibit hexagonal wurtzite structure without any secondary phases and that the crystallite average size, estimated by the Scherrer formula, is ranged between 13 and 30 nm. The main finding of this work is to show that the control of the crystalline growth orientation is possible simply by varying the solvent nature and/or the stabilizer molar ratio. These later parameters are therefore considered as key factors when seeking to develop the ZnO-based transducers. Actually, the ZnO thin films synthesized with propanol as solvent are oriented only along thec -axis; meanwhile, when using the isopropanol or ethanol, other preferential orientations appear. Additionally, the effect of MEA molar ratio (r ) has been studied on the propanol-derived films (the unfavorable case). It has been found that this parameter has a direct effect on the crystalline growth orientation of these films and that a new preferential orientation (100) appears at lowr . On the other hand, SEM images show the formation of homogeneous nanocrystalline thin films with an average grain size ranged between 19 and 35 nm. Moreover, the ZnO thin films exhibit a high transparency in the visible region, and the measured transmittance is ranged from 85 to 97%. However, the change of ZnO film orientation has no significant effect on the direct bandgap energy which is closed to 3.30 eV.